2007
DOI: 10.1515/bot.2007.019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic variation in Egregia menziesii over a latitudinal gradient

Abstract: This study characterized morphological variation in the kelp, Egregia menziesii, over a large geographic scale. Marked differences in rachis and lateral blade morphology were observed, suggesting local adaptation to the variable conditions of wave exposure and upwelling found across the study area. Observations of rachis type at different developmental stages indicated differential survivorship of smooth versus papillated individuals at sites with differing wave exposure. Variations in Egregia morphology have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…(The lack of significance for habitat as a single factor is likely due to the fact that overall magnitude of hsp70 expression was similar between the 2 habitats.) E. menziesii exhibits morphological variability among sites that seems to be a response to environmental conditions (Henkel et al 2007) and exhibited population specific responses to heat stress that varied with latitude in previous hsp70 investigations (Henkel & Hofmann 2008). Thus, the significant differences observed in this physiological measure between habitats in our study were not unexpected.…”
Section: Habitat Differencessupporting
confidence: 56%
“…(The lack of significance for habitat as a single factor is likely due to the fact that overall magnitude of hsp70 expression was similar between the 2 habitats.) E. menziesii exhibits morphological variability among sites that seems to be a response to environmental conditions (Henkel et al 2007) and exhibited population specific responses to heat stress that varied with latitude in previous hsp70 investigations (Henkel & Hofmann 2008). Thus, the significant differences observed in this physiological measure between habitats in our study were not unexpected.…”
Section: Habitat Differencessupporting
confidence: 56%
“…Morphological seaweed traits are associated with herbivory pressure, abiotic environment, and phylogenetic lineage, and their relationships with latitude are variable (Hay , Henkel et al. , Santelices et al. ), so clearly this would be an interesting question to further pursue.…”
Section: Discussionmentioning
confidence: 99%
“…The logistical benefits of using freeze-dried tissue in order to standardize food quality and allow us to assay seaweeds that were collected thousands of kilometers and months apart come at the cost of minimizing morphological traits. Morphological seaweed traits are associated with herbivory pressure, abiotic environment, and phylogenetic lineage, and their relationships with latitude are variable (Hay 1981, Henkel et al 2007, Santelices et al 2009), so clearly this would be an interesting question to further pursue. Pennings et al (2001) compared northern and southern Spartina populations and found that southern Spartina was significantly less palatable in fresh tissue assays (see also Long et al 2011), but when lyophilized tissue was tested, the significance was reduced (Siska et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2002, Henkel and Murray 2007, Henkel et al. 2007). Previous studies have found that Egregia compensated for this loss in a similar manner to Macrocystis by increasing the branching of fronds from the base, as well as forming new frond branches from damaged rachis edges (Black 1974, 1976).…”
Section: Figmentioning
confidence: 99%